Higher Body Mass Index Adversely Affects Knee Function After Anterior Cruciate Ligament Reconstruction in Individuals Who Are Recreationally Active. Issue 6 (November 2020) - Harput, Gulcan; Guney-Deniz, Hande; Ozer, Hamza; Baltaci, Gul; Mattacola, Carl
Abstract : Objective: Our aim was to investigate the effect of body mass index (BMI) levels on quadriceps and hamstring strength and functional outcomes up to 6 months after anterior cruciate ligament reconstruction (ACLR) with hamstring tendon autograft (HTG). Design: Prospective, controlled study. Setting: University clinical laboratory. Patients: Ninety-one participants who had undergone unilateral ACLR with HTG were divided into 2 groups according to their BMI. The participants whose BMI were between 18.5 and 24.9 kg/m 2 were included in group 1 (n = 50, age: 27.2 ± 6.7 years, BMI: 22.3 ± 1.6 kg/m 2 ) and those whose BMI > 24.9 kg/m 2 were included in group 2 (n = 41, age: 30.2 ± 6.9 years, BMI: 28.0 ± 2.4 kg/m 2 ). Interventions: Quadriceps and hamstring strength, functional performance including hop, jump, and balance performance, and IKDC score. Main Outcome Measures: Maximum voluntary isometric contraction of the quadriceps and hamstring muscles and the body mass were measured at 1, 3, and 6 months after surgery. Absolute peak torques and normalized peak torques to body weight for both limbs were recorded. Functional outcomes were evaluated at 6 months after surgery. Results: Normalized quadriceps strength improvement was lower in group 2 when compared with group 1 ( F (2, 178) = 6.23, P = 0.003). Group 2 also demonstrated lower scores in functional performance ( P < 0.05). Normalized hamstring and absolute quadriceps and hamstring strength improvement was not affected by higher BMI level ( P > 0.05). Conclusions: Higher BMI levels adversely affect quadriceps strength capacity and performance in patients who have undergone ACLR with HTG. Clinicians should consider BMI levels of patients when assessing and targeting muscle recovery because it could negatively affect the success of the ACLR rehabilitation. Abstract : Supplemental Digital Content is Available in the Text.